Prevalence of malocclusion in children aged 7 to 12 years - de Almeida, Marcio Rodrigues; Pereira, Alex Luiz Pozzobon; de Almeida, Renato Rodrigues; de Almeida-Pedrin, Renata Rodrigues; Filho, Omar Gabriel da Silva (FapUNIFESP (SciELO), 2011)
Objectives: To determine the prevalence of malocclusion in a group of 3,466 children aged 7 to 12 years enrolled in public schools in the cities of Lins and Promissão, in the state of São Paulo, Brazil. Methods: The sagittal relationships between dental arches, the transverse relationship between arches, and the vertical and horizontal relations of incisors were analyzed. The prevalence of diastemas, crowding and tooth losses were evaluated. Results: Among the types of malocclusion, 55.25% of the children had a Class I molar relationship, 38%, Class II, and 6.75%, Class III. The analysis of incisor relationships revealed 17.65% of open bite, followed by 13.28% of deep bite and 5.05% of anterior crossbite; 13.3% of the children had a posterior crossbite. The analysis of relationships between arches showed that 31.88% of the children had diastemas, 31.59%, crowding, and 4.65%, tooth losses.
Keywords: Angle classification; Epidemiology; Malocclusion; Normal occlusion